2019
DOI: 10.1111/jch.13537
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension‐induced subclinical vascular and cognitive changes are reversible—An observational cohort study

Abstract: Beside the well-known complications of poorly controlled, long-standing hypertension, milder abnormalities induced by early-stage hypertension have also been described. In our study, the authors examined the reversibility of changes induced by early-stage hypertension. The authors performed laboratory testing, ambulatory blood pressure monitoring, carotid intima-media thickness (IMT) measurement, evaluation of stiffness parameters, assessment of various cardiac and cerebral hemodynamic parameters during head-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
3
1
Order By: Relevance
“…Finally, in a study examining the reversibility of subclinical vascular and cognitive changes with antihypertensive treatment in newly diagnosed hypertensive patients Czuriga-Kovács et al . [34] found that patients performed better on neuropsychological assessment when compared to baseline after 1-year antihypertensive therapy, which was consistent with the present study results. Based on these results, future studies including patients with masked hypertension, newly diagnosed and long-term hypertension, can clarify this complex association in order to determine (1) whether the improvement with antihypertensive treatment in cognitive functions depends on the duration of hypertension, and (2) whether the improvement with antihypertensive treatment in cognitive functions in masked hypertensive and newly diagnosed hypertensive patients will deteriorate with time.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, in a study examining the reversibility of subclinical vascular and cognitive changes with antihypertensive treatment in newly diagnosed hypertensive patients Czuriga-Kovács et al . [34] found that patients performed better on neuropsychological assessment when compared to baseline after 1-year antihypertensive therapy, which was consistent with the present study results. Based on these results, future studies including patients with masked hypertension, newly diagnosed and long-term hypertension, can clarify this complex association in order to determine (1) whether the improvement with antihypertensive treatment in cognitive functions depends on the duration of hypertension, and (2) whether the improvement with antihypertensive treatment in cognitive functions in masked hypertensive and newly diagnosed hypertensive patients will deteriorate with time.…”
Section: Discussionsupporting
confidence: 93%
“…[27] Our research group reported previously that 1-year antihypertensive therapy results in significant improvement in vascular wall structure demonstrated by the reduction in carotid IMT. [28] In our present study, the reductive effect of 3-month ACE inhibition on carotid IMT did not reach a significant level.…”
Section: Discussioncontrasting
confidence: 72%
“…[38] A previous investigation by our study group showed that after 1 year of appropriate and effective antihypertensive therapy, normalized blood pressure was accompanied by an improved cognitive performance. [28] Although some studies provided hints that certain classes of antihypertensive drugs may be more effective than others at improving cognition or reducing cognitive decline, [3941] most of these studies were underpowered or without equivalent cognitive endpoints. [13] The current study demonstrated that the applied short-term (3-month) antihypertensive treatment with ACE inhibitors resulted in a significant improvement in executive function.…”
Section: Discussionmentioning
confidence: 99%
“…5 Therefore, the two guidelines share similar recommendations from the clinical point of view; the difference between them is the labeling of patients and the nomenclature used to define categories.Accordingly, our data also imply that better results in intimamedia thickness (IMT) reduction may be achieved when hypertension is treated at an earlier rather than a more advanced stage, as the reduction in IMT was more pronounced in patients with a mean blood pressure level below the median value at baseline. 6 One could say that the milder the blood pressure elevation, the better the reversibility of target organ damage represented by IMT.Regarding our study cohort, only three patients were recommended solely lifestyle changes without any drug therapy. It is unlikely that these patients were at high or very high risk as diabetic patients or those with any severe comorbidity had been excluded from the investigations.…”
mentioning
confidence: 94%
“…Accordingly, our data also imply that better results in intimamedia thickness (IMT) reduction may be achieved when hypertension is treated at an earlier rather than a more advanced stage, as the reduction in IMT was more pronounced in patients with a mean blood pressure level below the median value at baseline. 6 One could say that the milder the blood pressure elevation, the better the reversibility of target organ damage represented by IMT.…”
mentioning
confidence: 99%